PENGETAHUAN DAN PARITAS IBU BERHUBUNGAN DENGAN PENGGUNAAN KB SUNTIK 1 BULAN TAHUN 2021 - Vivi Oktari; Wiwiet Wulandari (Politeknik Kesehatan Kemenkes Bandung, 2025)
Globally, in 2022, the prevalence of contraceptive use was recorded at 65%. The purpose of this study is to determine the relationship between knowledge and maternal parity with the use of 1-month injectable birth control at PMB Hj. Zuniawaty Palembang in 2021. The research design used is a quantitative research that is an analytical survey with a cross-sectional design. The independent variable is knowledge and parity, the dependent variable is the use of 1-month Injectable Birth Control. The population is all mothers who came to PMB Hj. Zuniawati Palembang from November – December 2021 which amounted to 32 people. The sampling technique uses the accidental sampling technique, which is a sampling method by selecting respondents who happen to be there/found. The instrument useD a questionnaire. The data analysis carried out was univariate and bivariate. The chi-square test showed a significant relationship between knowledge (p=0.001) and parity (p=0.004) with the use of 1-month injectable birth control. Suggestions for PBMs can improve services, especially services for mothers who use 1-month injectable birth control and provide complete information about good knowledge of good 1-month injectable contraceptives and are willing to use injectable contraceptives as an effective contraceptive.